Changing risk factors for fluorosis among South Australian children - Spencer AJ, Do LG. (Journal compilation, 2008)
Research in the last decade has shown changing exposure patterns to discretionary fluorides and declining prevalence of fluorosis among South Australian children, raising the question of how risk factors for fluorosis have changed.